J.W. Spencer (1851-1921): His Life in Missouri and Georgia, and Work on Proglacial Lakes - Middleton, Gerard (Geoscience Canada, 2004)
SUMMARY In 1882, Spencer left Canada to become Professor of Geology and Mineralogy, and Director of the Natural History Museum at the State University of Missouri. His first task was to design and equip the new museum, part of a planned extension of the main university building. The museum was completed in 1884, but funding for specimens and furnishing was withheld as feuding between the administration and the State increased. In 1886, Spencer visited Europe, making observations in Norway which strengthened his belief that glaciers were ineffective agents of erosion. Spencer was forced to resign in 1887: he devoted that summer to intensive fieldwork in the Great Lakes region, tracing proglacial lake beaches. He was appointed Professor of Geology at the State University of Georgia in Athens in 1888 and devoted that summer to further fieldwork on the proglacial beaches. The summer of 1889 was spent in geological surveys for a new railroad in Georgia and Alabama, and in 1890 Spencer gave up his position as Professor to become State Geologist of Georgia. This position ended in 1893, because Spencer had mapped mainly Paleozoic rocks in the northwest part of the State, and was intolerant of demands that he yield to political pressures and spend more time on practical matters, including gold deposits. His two seasons of fieldwork (in 1887 and 1888) were the main basis for the numerous papers that he subsequently published that named proglacial lakes (e.g., Iroquois, Algonquin), described their post-glacial deformation, and discussed their origin. Spencer did not accept that the Great Lakes region was ever covered by thick ice sheets: he believed the proglacial lakes formed at sea level, and were not the result of ice-dams.